2014
DOI: 10.1117/1.jbo.19.8.085002
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence imaging device for real-time detection and tracking of pathogenic bacteria in a mouse skin wound model: preclinical feasibility studies

Abstract: Bacterial infection significantly impedes wound healing. Clinical diagnosis of wound infections is subjective and suboptimal, in part because bacteria are invisible to the naked eye during clinical examination. Moreover, bacterial infection can be present in asymptomatic patients, leading to missed opportunities for diagnosis and treatment. We developed a prototype handheld autofluorescence (AF) imaging device (Portable Real-time Optical Detection, Identification and Guidance for Intervention - PRODIGI) to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 23 publications
0
34
1
1
Order By: Relevance
“…Other methods to explore include use of radio frequency identification (RFID) signal fluctuations to detect in real-time the presence or absence of bacteria, though specific information on bacterial strains have not been demonstrated (ElMahgoub and Shaban, 2014). Additionally, an auto-fluorescent device utilizing a broadband white LED output and dual-wavelength LED detection array may be capable of real-time detection of bacteria and is currently in preclinical studies (Wu et al, 2014).…”
Section: Future Directionsmentioning
confidence: 99%
“…Other methods to explore include use of radio frequency identification (RFID) signal fluctuations to detect in real-time the presence or absence of bacteria, though specific information on bacterial strains have not been demonstrated (ElMahgoub and Shaban, 2014). Additionally, an auto-fluorescent device utilizing a broadband white LED output and dual-wavelength LED detection array may be capable of real-time detection of bacteria and is currently in preclinical studies (Wu et al, 2014).…”
Section: Future Directionsmentioning
confidence: 99%
“…Fluorescence image has been applied for assessment of connective tissue extracellular matrix in wounds (usually blue-green bands) (Douplik et al, 2010) and bacterial contamination (typically red wavelength ranges) (Wu et al, 2014). Fluorescence image has been applied for assessment of connective tissue extracellular matrix in wounds (usually blue-green bands) (Douplik et al, 2010) and bacterial contamination (typically red wavelength ranges) (Wu et al, 2014).…”
Section: Fluorescence Imagementioning
confidence: 99%
“…It was reported that accumulation of advance glycosylation end products (AGEs) produced autofluorescence . It is valuable for diagnosis and treatment of diabetes, clinical atherosclerosis, chronic kidney disease, and tissue wounds because of accumulation of AGEs during these diseases . This type of skin autofluorescence could be assessed with a special device‐AGE Reader, which has been known as a noninvasive marker for accumulation of AGEs.…”
Section: Introductionmentioning
confidence: 99%